The mathematics teacher in the digital era : an international perspective on technology focused professional development - Clark-Wilson, Alison, editor; Robutti, Ornella, editor; Sinclair, Nathalie, editor (Dordrecht ; Heidelberg : Springer, 2014)
Includes bibliographical references and index